Real World Effectiveness of fixed combination of glargine 100 U/ml and lixisenatide therapy in outpatients with Type 2 Diabetes: A Retrospective Cohort Study SOLO - M. B. Antsiferov; N. A. Demidov; M. A. Balberova; T. I. Safronova; O. A. Mishra; S. G. Magomedova (Сахарный диабет)
Background: The effectiveness and safety of a fixed combination of insulin glargine 100 ME/ml and lixisenatide for treatment of patients with type 2 diabetes (T2DM) has been demonstrated in randomized clinical trials, but there are still not enough data of it`s usage of it real clinical practice.Aim: To describe the baseline characteristics of patients with T2DM who started treatment with a fixed ratio combination of insulin glargine 100 ME/ml and lixisenatide in the period from November 2018 to July 2020, and to evaluate the effectiveness of using fixed combination of insulin glargine 100 ME/ml and lixisenatide in for 6–12 months of therapy in a real outpatient practice.Materials and methods: SOLO was a retrospective cohort multicentre study conducted in Russia, Moscow. Adults (≥18 years) with T2DM and HbA1c≥7% in case of availability of medical records during ≥180 days before and ≥1 HbA1c level during 150–210 days after start of treatment with Soliqua SoloStar® were eligible.Results: A total of 383 people with T2DM were included. Baseline characteristics were the following (mean±SD): age 59.9±8.3 years; BMI 36.4±6.3 kg/m2; proportion of patients with BMI≥35 kg/m2 — 52.2%; HbA1c 9.14±1.08%. 65% of patients received oral antidiabetic drugs (OAD) before start of treatment with fixed combination of insulin glargine 100 ME/ml and lixisenatide ; 31.3% of patients were switched from combination of OAD with basal insulin, 1.04% of patients received other therapy (GLP-1 RA, basal-bolus insulin treatment, basal insulin monotherapy), and 2.61% of patients did not receive any hypoglycemic therapy. HbA1c level was 7.78±0.8% after 6 months of treatment and 7.4±0.61% after 12 months. There was a significant decrease of body weight from the baseline value 101.62±20.64 kg by 1.96±4.03 kg at month 6 and by 3.13±4.71 kg at month 12 (p<0.001) Overall, 4 patients (1.04%) reported symptomatic hypoglycemia (glycemia ≤3.9 mmol/L); no episodes of severe hypoglycemia were registered.Conclusion: In a real-life setting in Russia, initiation of a fixed combination of insulin glargine 100 ME/ ml and lixisenatide in people with T2DM uncontrolled on OADs or combination of OADs with basal insulin resulted resulted in an improved glycemic control and body weight change with low risk of hypoglycemia compared to baseline